2014
DOI: 10.7883/yoken.67.191
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Behavior of HIV/AIDS among Females Sex Workers in Bangladesh: Survey in Rajshahi City

Abstract: SUMMARY: Female sex workers (FSWs) and their clients are one of the major sources of spread of HIV/AIDS in Bangladesh. The purpose of this study was to determine the rate of unprotected sex among FSWs in Rajshahi City, Bangladesh. A total of 200 FSWs were randomly selected for the survey from February to September 2012. The age range of FSWs was 16-41 years (average age, 24.52 ± 6.26 years), and the majority of these women (84.4z) were married. More than 88z of FSWs reported practicing unprotected sex because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 8 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…Surprisingly, several studies have shown the rate of HIV disease to be relatively low in Bangladeshi CSEWC (national rate 0.15% in 2014), although rates of Sexually Transmitted Infections (STIs) (chlamydia, syphilis, gonorrhoea and other infections) exceed 50 percent in CSEWC (Azim et al, 2008;Baral et al, 2012;Eva et al, 2007;Hosein & Chatterjee, 2007;Hossain et al, 2011;Islam & Congrove, 2008;Khairin et al, 2005;Mondal et al, 2008;Nessa et al, 2008;Rahman et al, 2000;Uddin et al, 2014).…”
Section: Men Women and Stis (Sexually Transmitted Infections)mentioning
confidence: 99%
“…Surprisingly, several studies have shown the rate of HIV disease to be relatively low in Bangladeshi CSEWC (national rate 0.15% in 2014), although rates of Sexually Transmitted Infections (STIs) (chlamydia, syphilis, gonorrhoea and other infections) exceed 50 percent in CSEWC (Azim et al, 2008;Baral et al, 2012;Eva et al, 2007;Hosein & Chatterjee, 2007;Hossain et al, 2011;Islam & Congrove, 2008;Khairin et al, 2005;Mondal et al, 2008;Nessa et al, 2008;Rahman et al, 2000;Uddin et al, 2014).…”
Section: Men Women and Stis (Sexually Transmitted Infections)mentioning
confidence: 99%
“…Female sex workers (FSWs) are most important vulnerable groups for getting and spreading TB, because they trade sex with their clients without any information of clients’ TB status in Bangladesh [1]. It was estimated in 2009 that the number of FSWs was 63 to 74 thousand in Bangladesh [2]. Usually, FSWs in Bangladesh trade sex in street, hotel, residence and brothel.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, FSWs in Bangladesh trade sex in street, hotel, residence and brothel. Hotel and residence based FSWs entertained an average of 61 clients per week in Bangladesh [2]. There are few brothels in Bangladesh, and Rajshahi is one of the cities where there is no brothel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations